A novel fuzzy PD plus repetitive control scheme for inverters - Li Jian; Kang Yong; Chen Jian (37th Intersociety Energy Conversion Conference Proceedings 2002, 2002)
A fuzzy PD plus repetitive control scheme for single-phase 400 Hz CVCF inverters is presented. The principle of the proposed control scheme is to use a repetitive controller, which performs satisfactorily in steady state, while a fuzzy PD controller improves transient performance whenever the system exhibits an oscillatory or overshoot behavior. The fuzzy PD controller preserves the simple linear structure of the conventional PD controller yet enhances its self-tuning control capability. The repetitive controller is synthesizing to minimize low-order harmonic distortion. Thus, the fuzzy PD controller and repetitive controller can be combined to take advantage of their positive attributes. The control scheme is implemented using a TI TMS320F240 DSP in a 400 Hz 6 kW prototype. Simulation and experimental results prove that the proposed control scheme can achieve not only low THD during steady-state operation but also fast transient response subject to load step change.